OVERVIEW OF C# - Rohdia, Taruna (IJRDO -Journal of Computer Science Engineering, 2015)
A type of programming in which programmers define not only the datatype of a data structure, but also the types of operations (functions) that can beapplied to the data structure. In this way, the data structure becomes an object thatincludes both data and functions. In addition, programmers can create relationshipsbetween one object and another. Object-oriented technology is becomingincreasingly popular in industrial software development environments. Thistechnology helps in the development of a software product of higher quality andlower maintenance costs. One of the principal advantages of object-orientedprogramming techniques over procedural programming techniques is that theyenable programmers to create modules that do not need to be changed when a newtype of object is added. A programmer can simply create a new object that inheritsmany of its features from existing objects.